Bruton tyrosine kinase inhibitors in B-cell lymphoma: beyond the antitumour effect - Haoran Wang; Hao Guo; Jingyi Yang; Yanyan Liu; Xingchen Liu; Qing Zhang; Keshu Zhou (Experimental Hematology & Oncology, 2022)
Abstract Targeting B-cell receptor signalling using Bruton tyrosine kinase (BTK) inhibitors (BTKis) has become a highly successful treatment modality for B-cell malignancies, especially for chronic lymphocytic leukaemia. However, long-term administration of BTKis can be complicated by adverse on- and/or off-target effects in particular cell types. BTK is widely expressed in cells of haematopoietic origin, which are pivotal components of the tumour microenvironment. BTKis, thus, show broad immunomodulatory effects on various non-B immune cell subsets by inhibiting specific immune receptors, including T-cell receptor and Toll-like receptors. Furthermore, due to the off-target inhibition of other kinases, such as IL-2-inducible T-cell kinase, epidermal growth factor receptor, and the TEC and SRC family kinases, BTKis have additional distinct effects on T cells, natural killer cells, platelets, cardiomyocytes, and other cell types. Such mechanisms of action might contribute to the exceptionally high clinical efficacy as well as the unique profiles of adverse effects, including infections, bleeding, and atrial fibrillation, observed during BTKi administration. However, the immune defects and related infections caused by BTKis have not received sufficient attention in clinical studies till date. The broad involvement of BTK in immunological pathways provides a rationale to combine BTKis with specific immunotherapies, such as immune checkpoint inhibitor or chimeric antigen receptor-T-cell therapy, for the treatment of relapsed or refractory diseases. This review discusses and summarises the above-mentioned issues as a reference for clinicians and researchers.